METHODS OF STUDENTS PROFESSIONAL MOTIVATION DEVELOPMENT ON DEPARTMENT OF THERAPEUTIC DENTISTRY - N.М. Ilenko; O.M. Boychenko (Ukrainian Medical Stomatological Academy, 2018)
The article emphasises the development of motives and needs of a medical student as one of the most relevant issues in motivation psychology for a future doctor. The importance of this problem is beyond a shadow of doubt, since the issue of the development of motives and needs is closely linked with the development of the individual on the whole. The motive can also be defined as the concept, which in a generalizing form says that there are many predilections. It activates the body, stimulates its behaviour and is aimed at determining what is needed. In the process of human activity, the personality develops and the environment in which the person lives is transformed. Needs are the driving force of personality development. Motives (predilections), needs and goals are components of the human's motivational sphere. Considering the motivation of educational activity, it must be emphasized that the concept of motive is closely related to the concept of purpose and need. Motivational sphere includes: the need for learning, the importance of learning, the motive to learn, purpose, emotions, attitude and interest. The ability to create situations which promote the interest in the teacher as well as in learning. The more active are the teaching methods, the easier it is for the students to get interested. One of such methods at the Department of Therapeutic Dentistry is the realization of a programme of practical classes for highly motivated students, whose goal is to develop practical skills related to the future profession of the dentist during the course of preliminary training. Nowadays requires not only to improve methods in which the principle of mere repetition is basic and leads to intellectual and physical overload of students, but by means of finding new, more effective methods of educational and cognitive activity of students, to form their professional motivation. The article is devoted to the questions of motivation of the future doctor and the formation of his needs for constant self-improvement during practical classes and the individual work beyond the requirements of the programme.